VERDI’S OPERA ‘A MASKED BALL’ – THE ORCHESTRAL DISCOURSE EXPRESSIVENESS AND DRAMATURGICAL IMPLICATIONS IN OUTLINING THE PROTAGONISTS - ADETU, Edith Georgiana; COROIU, Petruța Maria (Studia Universitatis Babes-Bolyai Musica, 2023)
The opera A Masked Ball’marks the end of the middle period in the work of Giuseppe Verdi and represents an important stage in the musical progress of the composer. It comprises a variety and an orchestral inventiveness much higher than any other of his previous works, and, more than ever, the score is consistent with the dramatical structure of the opera. Compared to some titles from the first period of creation, the outlining of the protagonists is not performed only by means of vocality. The subtlety of the orchestral music rounds off a rich sound picture, in accordance with the requirements of musical dramaturgy. This article addresses the structural, stylistic, and dramaturgical aspects found at the level of the orchestral discourse.